Web System for the Management of Clinical Laboratory Test applied to Health Facilities in Rural Areas - Mantilla Flores, Noelia Karina (2024)
When visiting health facilities in the interior of Peru, considered as rural areas, we mostly found many shortcomings in the management of health facilities, which is not allowing efficient management, one of the processes is the registration of clinical and pathological analysis, the information they have are in Excel books or notebooks, which makes it difficult to search for patient and processing reports, stopping the good service in health facilities and delays the patient waiting for their results. In this paper we present the design of a web system for the process of care in the clinical laboratory service in health facilities in rural areas, we present the details of the implementation, the main interfaces and a statistic related to the application.